Resource Based View (RBV) Analysis in Building Competitive Advantage in the SME Sector - Hidayat, Nuzul; Rahayu, Baiq Novrinda Dwi (Universitas Bumigora, 2024)
In an era of globalization characterized by rapid technological developments and rapid changesin consumer preferences, achieving and maintaining competitive advantage is a major challenge forcompanies. The highly competitive business world requires every organization, both large and small, tocontinue to adapt and design the right strategies to stay ahead in the market. The purpose of this studyis to analyze resources that have the potential to generate sustainable competitive advantage throughthe Resource-based View approach to find out what resources Inifood has to get core competencies as asource of Competitive Advantage. The method used in this research is descriptive qualitative with a casestudy approach. The analytical tool in this study uses the Valuable, Rarity, Imitability, and OrganizationFramework (VRIO) to achieve Sustainable Competitive Advantage. The results of this study found thatInifood has four resources and one capability at the temporary competitive advantage level. Then, there isone resource at the Unused Competitive Advantage level (unused/too expensive competitive advantage).Finally, three resources and three capabilities are at the Sustainable Competitive Advantage level. Thisresearch contributes to ensuring that this competitive advantage is important to maintain. This also canbe an implication for businesses that must manage, develop, and evaluate the 6 main advantages well andmake them the main focus.